Znalecké posudky, jejich přezkoumatelnost, verifikace a vady - Sadílek, Augustin (Akademické nakladatelství CERM, 2019)
Znalecké posudky, jejich přezkoumatelnost, verifikace a vady

Expert Opinions, their Reviewability, Verification and Faults
Expert Opinions, their Reviewability, Verification and Faults
Keywords: znalec; znalecký posudek; oceňování; cena; majetek; nemovitost; přezkoumatelnost; verifikace; supervize; vady; expert (forensic expert); expert opinion (expert report); valuation; price; property; real estate; reviewability; verification; supervision; faults